From Democratic (Citizenship) Education to Participative Democracy? Youth’s Difficult Way to Active Citizenship - Mrozowska, Sylwia (Wydawnictwo Naukowe WNPiD UAM, 2019)
In this article we make an attempt to join a discussions on the political and social activity of young people in contemporary polyarchies. On the basis of the assumption that the condition for the active fulfilment of civic functions are cognitive skills and the ability to communicate which the individual improves in the education process and through participation in social phenomena, we are trying to find the answer to the following questions: how is participation perceived in today’s polyarchies, what can be the determinants of youth’s political and social involvement, why do European international organisations – the Council of Europe and the European Union – take measures to activate European youth. In the first part of the article, we focus on democratic participation and try to recognise its role in selected models of democracy. Then we analyse selected aspects of youth electoral absenteeism. We cite examples of the activities of the Council of Europe and the European Union in the field of the youth democratic (civic) activation with an indication of the reasons for this activity. Finally, we point to the relationship between the political and social participation of young people and the condition of modern European polyarchies.

W artykule podejmujemy próbę włączenia się do dyskusji na temat aktywności politycznej i społecznej młodzieży we współczesnych poliarchiach. Wychodząc z założenia, że warunkiem aktywnego spełniania funkcji obywatelskich są umiejętności poznawcze i zdolności komunikowania się, które jednostka doskonali w procesie kształcenia się i poprzez uczestniczenie w zjawiskach społecznych staramy się znaleźć odpowiedź na następujące pytania: w jaki sposób postrzegane jest uczestnictwo w dzisiejszych poliarchiach? jakie mogą być determinanty angażowania się politycznego i społecznego młodzieży? Dlaczego europejskie organizacje międzynarodowe – Rada Europy i Unia Europejska – podejmują działania z zakresu aktywizowania młodzieży europejskiej? W pierwszej części artykułu uwagę koncentrujemy na uczestnictwie demokratycznym i staramy się poznać jego rolę w wybranych modelach demokracji. Następnie analizujemy wybrane aspekty absencji wyborczej młodzieży. Przywołujemy przykłady aktywności Rady Europy i Unii Europejskiej w zakresie aktywizowania demokratycznego (obywatelskiego) młodzieży wraz ze wskazaniem przyczyn tej aktywności. W końcu wskazujemy na związek pomiędzy uczestnictwem politycznym i społecznym młodzieży a kondycją współczesnych poliarchii europejskich.
Od edukacji demokratycznej (obywatelskiej) do demokracji partycypacyjnej? Trudna droga do aktywnego obywatelstwa młodzieży
Keywords: democratic participation; democratic education; youth political participation; partycypacja demokratyczna; edukacja demokratyczna; partycypacja polityczna młodzieży